Toeplitz determinant for a subclass of tilted starlike functions with respect to conjugate points - Nur Hazwani Aqilah Abdul Wahid; Daud Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Let ()*,,,cSABαδ denote the class of analytic and univalent functions in an open unit disk of the form ()2nnnfzzaz∞==+Σ and satisfy ()()11sin1izfzAzeigztBzααδδα′+−−+where()()() ,2fzfzgz+=cos0,tαδαδ=−>0<1,δ≤2πα< and 11.BA−≤<≤ This paper presents the coefficient bounds for functions in ()*,,,cSABαδ using symmetric Toeplitz determinants ()22,T()32T and ()31.T The results obtained generalize the results for some existing subclasses in the literature.